A 2-year retrospective study of endodontic microsurgery for bone fenestration - Zhang, Lei; Wang, An-na; Zheng, Han; Sun, Qiong; Guan, Lixia; Zhang, Fuhua (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the clinical efficacy and relevant prognostic factors of endodontic microsurgery in cases with bone fenestration. Method: The retrospective cohort study was conducted at the Endodontic Department of Hefei Stomatological Hospital, China, and comprised data of patients who underwent endodontic microsurgery between October 1, 2019, and October 31, 2023, who had a follow-up duration of at least 24 months. The patients were grouped according to age, gender, jaw position, tooth position, presence or absence of sinus tract, presence or absence of root canal posts, root canal filling quality, periapical lesion type, bone fenestration or mucosal fenestration, the presence or absence of periodontal disease, and guided tissue regeneration. Factors affecting the healing of bone fenestration with endodontic microsurgery were identified. Data was analysed SPSS 23. Results: Of the 52 teeth from 42 patients, 27(52%) belonged to females and 25(48%) to males. Overall, 32(61.5%) teeth were from patients aged >32 years and 20(38.5%) from those aged <28 years (p>0.05). The mean ± SD follow-up period was 29 ± 4.2 months (range: 24-40 months). Mucosal fenestration was involved in 13(25%) cases. The success rate of endodontic microsurgery was 48(92.3%). Periodontal disease and guided tissue regeneration were the factors that affected endodontic microsurgery healing for teeth with bone fenestration (p<0.05). Conclusion: Endodontic microsurgery was an effective method for treating complex periapical lesions, such as bone or mucosal fenestration. Associated periodontal disease and guided tissue regeneration were the factors significant influencing the early healing of bone fenestration with endodontic microsurgery. Key words: Bone fenestration, Mucosal fenestration, Endodontic microsurgery, GTR.